8‐mm versus 10‐mm diameter self‐expandable metallic stent in bilateral endoscopic stent‐in‐stent deployment for malignant hilar biliary obstruction. (22nd January 2015) - Naitoh, Itaru; Nakazawa, Takahiro; Ban, Tesshin; Okumura, Fumihiro; Hirano, Atsuyuki; Takada, Hiroki; Togawa, Shozo; Hayashi, Kazuki; Miyabe, Katsuyuki; Shimizu, Shuya; Kondo, Hiromu; Nishi, Yuji; et al.
Abstract: Background: We aimed to clarify the clinical benefits of using 8‐mm versus 10‐mm diameter self‐expandable metallic stent (SEMS) in bilateral endoscopic stent‐in‐stent (SIS) deployment for malignant hilar biliary obstruction (MHBO). Methods: A total of 72 consecutive patients with MHBO treated by endoscopic bilateral SIS deployment were enrolled. The 8‐mm and 10‐mm diameter SEMSs were used in 37 patients (8‐mm group) and 35 patients (10‐mm group), respectively. We retrospectively compared technical success, functional success, complications, successful re‐intervention, time to recurrent biliary obstruction (RBO) and survival time between two groups. Results: There were no significant inter‐group differences in terms of technical success (8‐mm vs. 10‐mm group, both 100%), functional success (96% vs. 100%), early (5% vs. 9%) and late (19% vs. 14%) complications other than RBO, and successful endoscopic re‐intervention (94% vs. 100%), respectively. Time to RBO (median: 198 days vs. 222 days; log‐rank, P  = 0.440) and survival time (median: 186 days vs. 235 days; log‐rank, P  = 0.883) did not differ significantly between the two groups. However, the success rate of endoscopic bilateral revisionary stent insertion for RBO was significantly higher in the 10‐mm compared to the 8‐mm group (68% vs. 31%; P  = 0.044). Conclusions: The 10‐mm diameter SEMS is more suitable with regard to endoscopic re‐intervention.